Examining dentists' attitudes about ethical principles in everyday practice - Šljivić Katarina Z.; Nikolić Maja D.; Krunić Nebojša S. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2020)
Introduction: Patient care, knowledge of medical law and compliance with the law contribute to more efficient dealing with the ethical dilemmas often faced by today's dentists. Moreover, when it comes to determining 'the best' dental treatment, patients also play a certain role. The aim of the research was to examine the attitudes of Serbian dentists related to ethical dilemmas in everyday practice, so as to determine the factors that affect solving the dilemmas. Materials and methods: The paper was carried out as a cross-sectional study. The research included 88 respondents, 42 final year dentistry students at the Faculty of Medicine in Niš and the Faculty of Dentistry in Belgrade and 46 dentists from both private and state practice. The first part of the questionnaire included socio-demographic information on the respondents, and the second part consisted of 7 closed-ended questions about particular ethical dilemmas. Statistical analysis was done using Excel from Microsoft Office and SPSS, version 18.0. Results: There were no significant differences regarding the students and dentists' answers about individual ethical aspects, except for the domain of question 2b, whether the oral surgeon should have extracted both teeth on the patient's request, although the patient had a heart disease. A statistically significant difference was found (ch 2 =18,834, p<0,0001) regarding the dentists' answers in comparison with the students' answers. Conclusion: The knowledge about ethical principles of the majority of the respondents was satisfying. A smaller proportion of the respondents were not sufficiently aware of the importance of applying ethical principles in dental practice. Consequently, it is necessary to promote education programs about medical ethics for dentists and dentistry students.